CLIP4 Shows Putative Tumor Suppressor Characteristics in Breast Cancer: An Integrated Analysis - Fan, Yu; He, Lijia; Wang, Yu; Fu, Shaozhi; Han, Yunwei; Fan, Juan; Wen, Qinglian (Frontiers in Molecular Biosciences, 2021)
Background: CAP-Gly domain containing linker protein family member 4 (CLIP4) plays an important role in cancers. However, its expression, prognostic value, and biological effect in breast cancer remain unclear. Methods: Data on patients diagnosed with breast cancer were retrieved from the TCGA-BRCA and other public omics databases. The expression profile of CLIP4 was analyzed using Oncomine, bc-GenExMiner, and TCGA. The prognostic value of CLIP4 was determined by Kaplan-Meier Plotter and Human Protein Atlas. Identification of genes co-expressed with CLIP4 and potential mechanism analyses were performed using UALCAN, STRING, Metascape, and GSEA. The epigenetic characteristics of CLIP4 were determined by DiseaseMeth and MEXPRESS. Results: CLIP4 was downregulated and its expression was negatively correlated with estrogen receptor, progesterone receptor, HER2 status, Nottingham prognostic index, and Scarff-Bloom-Richardson grade in breast cancer, whereas it was positively linked to basal-like and triple negative breast cancer status. Ectopic expression of CLIP4 was related with poor prognosis. In the analysis of genes co-expressed with CLIP4, GSEA showed that the Hedgehog, JAK-STAT, ERBB, Wnt signaling pathway, cell adhesion molecules, and pathways in cancer were dissimilarly enriched in the CLIP4 expression high phenotype. Analysis of the genetics and epigenetics of CLIP4 indicated that its expression was negatively correlated with DNA methylation. Conclusion: Methylated CLIP4 may be a novel prognostic and therapeutic biomarker for breast cancer.